The Effect of Communication and Job Satisfaction Towards the Performance of Civil Servants in Jambi Province, Indonesia - Muhammad Oceano Fauzan; Disman Disman; Tjutju Yuniarsih; Budi Santoso (Institut Pemerintahan Dalam Negeri, 2020)
This research examines the effect of communication and job satisfaction on the performance of civil servants in Jambi Province in order to provide adequate input and knowledge for readers. Data were obtained by distributing questionnaires to employees with a Likert' scale of 1 – 2, used for analysis. The results showed that communication (X1) has no partial effect on performance (Y), while job satisfaction (X2) has a positive and significant effect on performance (Y). Similarly, there is a partial effect between communication (X1) and job satisfaction (X2) variables towards the performance (Y) on the Manpower and Transmigration Office employees in Jambi Province.